2021
DOI: 10.3390/magnetochemistry7110141
|View full text |Cite
|
Sign up to set email alerts
|

Large Perpendicular Exchange Energy in TbxCo100−x/Cu(t)/[Co/Pt]2 Heterostructures

Abstract: In order to realize a perpendicular exchange bias for applications, a robust and tunable exchange bias is required for spintronic applications. Here, we show the perpendicular exchange energy (PEE) in the TbxCo100−x/Cu/[Co/Pt]2 heterostructures. The structure consists of amorphous ferrimagnetic Tb–Co alloy films and ferromagnetic Co/Pt multilayers. The dependence of the PEE on the interlayer thickness of Cu and the composition of Tb–Co were analyzed. We demonstrate that the PEE can be controlled by changing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Ranjbar et al also reported a large perpendicular exchange energy in rare earth alloys, Tb x Co 100−x /Cu/[Co/Pt] 2 heterostructures [11]. They controlled two competing mechanisms: the effect of Tb content on saturation magnetisation and the coercivity of heterostructures.…”
mentioning
confidence: 97%
“…Ranjbar et al also reported a large perpendicular exchange energy in rare earth alloys, Tb x Co 100−x /Cu/[Co/Pt] 2 heterostructures [11]. They controlled two competing mechanisms: the effect of Tb content on saturation magnetisation and the coercivity of heterostructures.…”
mentioning
confidence: 97%